CSR&COVID19 – How do they work together? Perceptions of Corporate Social Responsibility transformation during a pandemic crisis. Towards smart development - Lopata, Ewelina; Rogatka, Krzysztof (Bulletin of Geography. Socio-economic Series, 2021)
Nowadays, enterprises that are looking to achieve market success and maximise profits must not only offer good products or provide superior quality services, but also pay close attention to the environment in which they operate. One of the manifestations of concern for the broadly understood environment (society, environment) is Corporate Social Responsibility (CSR). For a good number of years, we have been observing changes in CSR trends, but the situation today demands that organisations update the existing lines of action and meet a whole new level of challenges. This article aims to present the results of case studies of company activities in CSR, as well as a social perception of CSR activities. It also seeks to draw attention to the transformation of ideas during the socio-economic crisis caused by the coronavirus pandemic. In order to reach the objective of the study, we used the Computer Assisted (Aided) Web Interviews (CAWI) method. This choice was dictated by the pandemic situation in the country. The research shows that there is a noticeable transformation of the focus of socially responsible activities from a global to a local approach centred around smart development. The study also concludes that the society expects that activities under this approach will be continued in the future. The outcomes also indicate that the pandemic situation has necessitated the introduction of entirely new solutions (among others, remote working) that were not previously perceived as feasible but now have a chance to develop further